K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

13 tháng 10 2021

Trả lời:

\(x^2-1=\left(x-1\right)\left(x+1\right)\)

...

2 tháng 10 2016

Đề sai nhé .Sửu lại

\(x^2-4x^2y^2+4+4x\)

\(=\left(x^2+4x+4\right)-4x^2y^2\)

\(=\left(x+2\right)^2-\left(2xy\right)^2\)

\(=\left(x+2+2xy\right)\left(x+2-2xy\right)\)

 

 

3 tháng 7 2019

\(x^8+3x^4+4\)

\(=\left(x^8-x^6+2x^4\right)+\left(x^6-x^4+2x^2\right)+\left(2x^4-2x^2+4\right)\)

\(=x^4\left(x^4-x^2+2\right)+x^2\left(x^4-x^2+2\right)+2\left(x^4-x^2+2\right)\)

\(=\left(x^4+x^2+2\right)\left(x^4-x^2+2\right)\)

3 tháng 7 2019

\(4x^4+4x^3+5x^2+2x+1\)

\(=\left(4x^4+2x^3+2x^2\right)+\left(2x^3+x^2+x\right)+\left(2x^2+x+1\right)\)

\(=2x^2\left(2x^2+x+1\right)+x\left(2x^2+x+1\right)+\left(2x^2+x+1\right)\)

\(=\left(2x^2+x+1\right)^2\)

3 tháng 11 2018

=X^7+x^6+x^5=x^4+x^3+x^2+1-x^6-x^5-x^4-x^3
=x^5(x^2=x+1)+(x^2+1)-x^4(x^^2-x+1)
=(x^2+x+1)(x^5+x^2-x^4)-(x-1)(x^2+x+1)
=(x^2+1+x)(x^5+x^2-X^4-x+1) 
mik lm rồi nên chắc đúng

3 tháng 11 2018

\(x^7+x^2+1=x^7+x^6+x^5-x^6-x^5-x^4+x^4+x^2+x+1-x\)

\(=x^5\left(x^2+x+1\right)-x^4\left(x^2+x+1\right)+x\left(x^3-1\right)+\left(x^2+x+1\right)\)

\(=x^5\left(x^2+x+1\right)-x^4\left(x^2+x+1\right)+x\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^5-x^4+x^2-x+1\right)\)